Relationship Between Heritage History And Smoking Habits With Hypertension Incidence - Indirwan Hasanuddin; Zainab (Jurnal Life Birth, 2023)
Hypertension is a systemic blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. In the elderly population, hypertension is defined as a systolic pressure of 160 mmHg and a diastolic pressure of 90 mmHg. The purpose of this study was to determine the relationship between heredity and smoking habits with the incidence of hypertension. This type of research is quantitative with an analytic descriptive design using a cross sectional study approach, which wants to know the relationship between one variable and another. The variables in question are the independent variables and the dependent variables. The analytical test used is bivariate analysis, which is an analysis that connects two variables, namely the independent variable and the dependent variable. Bivariate analysis using the Chi Square test using α = 5% using the SPSS version 16 computer program. The results of this study were that there was a relationship between the patient's hereditary history and the incidence of hypertension (p=0.001). There is a relationship between the patient's smoking habit and the incidence of hypertension (p=0.007). It is hoped that the information on the results of this study can be used as additional material to enrich knowledge and reference needs for community nursing science that causes hypertension. Keywords: Hypertension; Descendants; Smoking habit